Multiple screen addiction among health sciences faculty students: An examination of the relationship with eating disorders, ultra processed food consumption, and e-healthy diet literacy - Serkan Aslan; Özge Esgin; Seda Nur Aktaş; Dilara Kudret; Senagül Süleymanoğlu (Clinical Science of Nutrition, 2026)
Objective: Screen addiction is a significant public health problem linked to various health issues, particularly affecting children and young people. This study aimed to evaluate the relationship between screen addiction among university students and eating disorders, ultra-processed food consumption, and nutritional literacy. Methods: The study was carried out among students enrolled in the Faculty of Health Sciences at Erzurum Technical University. Participants were administered the Eating Disorder Examination Scale (EDE-Q-13) short form, the e-Healthy Diet Literacy Scale (e-HDLQ), the Multiple Screen Addiction Scale (MSAS), and the Screening Questionnaire of Highly Processed Food Consumption (sQ-HPF) questionnaires face-to-face. Results: This cross-sectional study included 233 participants (26.6% men, 73.4% women; mean age 21.1±1.6 years). Multiple screen addiction was identified in 40.7% of the students. Multiple screen addiction showed weak negative correlations with EDE-Q13 (r=-0.197) and sQ-HPF (r=-0.134) and a weak positive correlation with e-HDLQ (r=0.210) (p<0.01). The relationship between MSAS score and sQ-HPF, EDE-Q-13, and e-HDLQ is examined using multivariate multiple regression analysis adjusted for age, gender, meal skipping status, and BMI (Wilks’ λ = 0.913, F(3, 223) = 7.054, p < 0.001, partial η2 = 0.087). The findings showed a negative correlation between MSAS and sQ-HPF (B = −0.027, SE = 0.013, p = 0.045, partial η2 = 0.018) and EDE-Q-13 (B = −0.209, SE = 0.065, p = 0.001, partial η2 = 0.044) and a positive significant relationship with e-HDLQ (B = 0.079, SE = 0.032, p = 0.016, partial η2 = 0.026). Conclusion: Multiple screen addiction was independently associated with fewer eating disorder symptoms, lower ultra-processed food consumption, and higher e-HDLQ scores. However, e-HDLQ itself was not significantly correlated with either eating disorder symptoms or ultra-processed food consumption, suggesting that literacy alone does not fully explain these associations.